Impactos ambientais decorrentes de atividades minerárias: o caso do arsênio em Vila de Elesbão, Amapá-AP - BATISTA, Edson José Louzada (2019)
Mining activity is known to the earliest times of human civilization contributing to the development and modernization. In the present scenario it remains vitally important for those regions that use the exploitation of various minerals resulting from this activity. However, as in the past and more intensified in the current context, it has generated impacts on social and environmental sphere. In recent years, many problems related to the health of the population in the vicinity of large mineral projects figured on the world stage. At the regional level, can be emphasized to contamination by arsenic in Elesbão village locality, in Amapá state, situated on the banks of the canal north of the mouth of the Amazon River near the port of Santana. There, the ICOMI mining (Industry and Trade of ores SA) during the years 1953 to 1998, he served in the exploitation and processing of manganese ore possibly contributing to the contamination in the town of Elesbão. Caused by leakage of toxic substances including arsenic (As), due to the rupture of the tailings containment dam of low grade manganese ore. It stockpiles after the pelleting process at ambient conditions. The waste ore suffered chemical processes (oxidation reactions) and subsequent leaching of As, a heavy metal and toxic contaminating soils and waters of the regions attached to the enterprise. (Scarpelli 2003). There are several records of health problems reported by the local population, which may be related to environmental liabilities left by ICOMI during the years of work in the region. Several studies over the years have found high concentrations of arsenic in the environment, however, few references made to arsenic as a causative agent of serious pathologies recorded. The Arsenic is toxic in above 1 μg/L concentrations in humans indicate a chronic intoxication, while values from 1 to 2 μg/L characterize acute intoxication. The case occurred in Elesbão village locality can be seen as an example of impacts generated by waste mining ventures.